Effect of thyme, lemongrass and rosemary essential oils on Aspergillus flavus in cauliflower seeds - Nakada-Freitas, Pâmela G. [UNESP]; Santos, César Augusto [UNESP]; Magalhães, Thalita Helena [UNESP]; Bustamonte, Stefani S. [UNESP]; Dos Santos, Danielle Carla [UNESP]; Cardoso, Antonio Ismael Inácio [UNESP]; Amador, Talita S. [UNESP]; Lanna, Natália de BL; Bardiviesso, Estefânia M. [UNESP]; Catão, Hugo Cesar RM (FapUNIFESP (SciELO), 2022)
Due to the action of essential oils of thyme, lemongrass and rosemary against microorganisms and few studies on them in seed treatment, this study is proposed with vegetable seed. Therefore, the aim was to evaluate the effect of treatments with essential oils of thyme, lemongrass and rosemary on cauliflower seeds, inoculated with Aspergillus flavus. Three essential oils were used, at concentrations 0.0; 0.4; 0.8; 1.6 and 2.0%, arranged in a 3x5 factorial scheme, in a completely randomized design, with four replications. The essential oils of thyme (1.8%) and lemongrass (1.9%) had a fungistatic effect against A. flavus in cauliflower seeds. Thyme essential oil at 2.0% and lemongrass at 1.6% didn’t affect the physiological quality of seeds, being promising in the treatment of organic seeds. On the other hand, rosemary essential oil, despite not affecting germination and little affecting seed vigor, wasn’t efficient in controlling the pathogen.
Efeito de óleos essenciais de tomilho, capim-limão e alecrim sobre Aspergillus flavus em sementes de couve-flor
Keywords: Brassica oleracea var. botrytis; Cymbopogon citratus; Rosmarinus officinalis; Thymus vulgaris